Digitalisation of learning: a driving force for higher education modernisation or a humanitarian threat? - Titarenko, Larissa G. (Journal of the Belarusian State University. Sociology, 2022)
The article discusses the problems of modernisation of the system of higher education in the Republic of Belarus related to the implementation of digital forms and methods of education. The inextricable link between the digitalisation of education and the ongoing fourth industrial revolution is revealed. On the basis of empirical data from studies carried out at Belarusian State University, it is shown that Belarusian and foreign students have increased their level of knowledge, skills and competencies in the use of information and communication technologies during a year of study in a pandemic period. Students appreciate the transfer to distance methods of a significant proportion of classes. The author noted that effective digitalisation of education contributes to the growth of the competitiveness of educational institutions. It is concluded that the active use of digitalisation is consistent with the goals of modernisation of the higher education system and does not pose a significant threat to the self-development of students. The results obtained can be used in research of the digitalisation of higher education in Belarus and other EAEU countries, and in teaching the Belarusian and foreign students studying in Belarusian universities.